Evidence of altered depression and dementia‐related proteins in the brains of young rats after ovariectomy. Issue 6 (9th August 2018) - Fang, Ying‐Yan; Zeng, Peng; Qu, Na; Ning, Lin‐Na; Chu, Jiang; Zhang, Teng; Zhou, Xin‐Wen; Tian, Qing
Abstract: Menopause, a risk factor for brain dysfunction in women, is characterized by neuropsychological symptoms including depression and dementia, which are closely related to alterations in different brain regions after menopause. However, little is known about the variability in pathophysiologic changes associated with menopause in the brain. Here, we observed that menopause in rats induced by bilateral ovariectomy (OVX) showed depressive and dementia‐related behaviors along with neuronal loss in the prefrontal cortex (PFC), hippocampus (HIP), hypothalamus (HYP), and amygdala (AMY) by Nissl staining. Meanwhile, by immunohistochemical staining, increased microglia in the HIP and AMY and increased astrocytes in the PFC, HYP, and AMY were shown. Using quantitative proteomics, we identified 146 differentially expressed proteins in the brains of OVX rats, for example, 20 in the PFC, 41 in the HIP, 17 in the HYP, and 79 in the AMY, and performed further detection by western blotting. A link between neuronal loss and apoptosis was suggested, as evidenced by increases in adenylate kinase 2 (AK2), B‐cell lymphoma 2 associated X (Bax), cleaved caspase 3, and phosphorylated p53 and decreases in Huntingtin‐interacting protein K, hexokinase, and phosphorylated B‐cell lymphoma 2 (Bcl‐2), and apoptosis might be triggered by endoplasmic reticulum stress (probed by increased glucose‐regulated protein 78 (GRP78), cleaved caspase 12, phosphorylated protein kinase R (PKR)‐like endoplasmic reticulum kinase, inositol‐requiring enzyme‐1 and activating transcription factor 6), and mitochondrial dysfunction (probed by increased cytochrome c and cleaved caspase 3 and decreased sideroflexin‐1 (SFXN1) and NADH dehydrogenase (ubiquinone) 1 α subcomplex 11 (NDUFA11)). Activation of autophagy was also indicated by increased autophagy‐related 7, γ‐aminobutyric acid (GABA) receptor‐associated protein‐like 2, and oxysterol‐binding protein‐related protein 1 and confirmed by increased microtubule‐associated protein light chain 3 (LC3II/I), autophagy‐related 5, and Beclin1 in the HIP and AMY. In the AMY, which is important in emotion, higher GABA transporter 3 and lower vesicular glutamate transporter 1 levels indicated an imbalance between excitatory and inhibitory neurotransmission, and the increased calretinin and decreased calbindin levels suggested an adjustment of GABAergic transmission after OVX. In addition, cytoskeletal abnormalities including tau hyperphosphorylation, dysregulated Ca² + signals, and glutamic synaptic impairments were observed in the brains of OVX rats. Collectively, our study showed the changes in different brain regions related to depression and dementia during menopause. Abstract : The variability in pathophysiologic changes in different brain regions, for example, the prefrontal cortex (PFC), hippocampus (HIP), hypothalamus (HYP), and amygdala (AMY), of rats after menopause were studied. Rats with bilateral ovariectomy (OVX) showed dementia and depression with neuronal loss in PFC/HIP/HYP/AMY, increased astrocytes in PFC/HYP/AMY, and increased microglia in HIP/AMY. Endoplasmic reticulum (ER) stress, autophagy dysregulation, mitochondrial dysfunction, and Ca 2+ signal dysregulation were involved in apoptosis, cytoskeletal abnormalities, and synaptic impairments in the brains of OVX rats. Furthermore, myelin injury in HIP/HYP/AMY, neurodegeneration with cytoskeletal abnormalities and synaptic impairments in HIP/HYP/AMY, and excitatory/inhibitory dysregulation in AMY were also found.